Sistem Pendukung Keputusan Pemilihan Guru Terbaik Menggunakan Metode MOORA (Studi Kasus: TK Persiwa II) - Tahlia Jelita Putri; Nasrul Hidayah (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
TK Persiwa II has not conducted a routine best teacher selection due to the absence of standard procedures and clear measurement tools, leading to subjective evaluations. This study aims to build a web-based Decision Support System (DSS) to automate the recommendations for the best teacher. The method applied is Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA), which processes six evaluation criteria categorized into benefit and cost attributes. The system was developed using the Waterfall model with PHP programming language and MySQL database. The final result of this research is a DSS application capable of generating automatic teacher ranking reports. The implementation of this system successfully assists the principal in making the best teacher selection decisions more transparently, objectively, and accountably.